Can a bonus overcome moral hazard? Experimental evidence from markets for expert services - Vera Angelova; Tobias Regner (Friedrich Schiller University Jena, 2018)
Interactions between players with private information and opposed interests are often prone to bad advice and inefficient outcomes, e.g. markets for financial or health care services. In a deception game we investigate experimentally which factors could improve advice quality. Besides advisor competition and identifiability, we add the possibility for clients to make a voluntary payment, a bonus, after observing advice quality. While the combination of competition and reputation concerns achieves the highest rate of truthful advice, we observe a similar effect, when the bonus is combined with one of them. Thus, our results suggest that a voluntary component can act as a substitute for either competition or reputation, decreasing moral hazard.
Keywords: C91; D03; D82; G20; I11; 330; asymmetric information; principal-agent; expert services; deception game; sender-receiver game; reciprocity; reputation; experiments; voluntary payment; competition